(untitled) (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted on 18 male kids of similar age (2-3 months) and body weight (6.32 to 7.27 kg) to elucidate the effect of selenium yeast and sodium selenite supplementation on serum minerals and vitamin-E. Kids were randomly divided into three equal groups and fed a basal diet consisted of concentrate mixture and oat straw to meet their nutrient requirement. Group I served as control, without any supplementation and groups II and III were supplemented with 0.3 mg selenium/kg DM as Selenium yeast and sodium selenite respectively. Experimental feeding lasted for 180 days. Blood samples were collected on day 0, 60,120 and 180 days to study the serum minerals and vitamin-E. Results revealed significant (P<0.05) increased in serum selenium and vitamin E concentration in supplemented groups than control. Serum calcium, phosphorus, iron, copper, zinc, manganese were similar (P>0.05) among the three groups. It may be concluded that supplementation of 0.3 ppm selenium as selenium yeast and sodium selenite enhanced serum selenium and vitamin E concentration without affecting other serum minerals in goats.